"Patrzył na wszystko jakby przez wizjer" - fotografia w "Walcu z Baszirem" Ariego Folmana - Powierska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
“He looked at everything as if through an imaginary camera” – Photography in Ari Folman’s Waltz with Bashir The article analyzes the theme of photography in Ari Folman’s Waltz with Bashir (2008). It shows the relation between photography and narration as well as similarities between the way the photographic medium functions and the mechanisms of trauma. The author points out that Folman’s documentary film uses the theme of photography as a metaphor for the characters’ emotional distance to what they experience.